The factors that led to NATO’s military intervention in Libya in 2011 - Κλειδαρά, Μαρία (Πανεπιστήμιο Πελοποννήσου, 2018)
Libya is an oil rich Arab country, located in the North Africa and ruled by Colonel Muamar Qaddafi since 1969. In 2011 Libya faced a bloody civil war between Qaddafi forces and the rebels who banded their forces against the colonel as an outcome of the Arab Spring, the revolutionary wave that took part in many Arab countries during that year. NATO’s military intervention in Libya during 2011 was initially aimed to stop the civil war that broke out. In this effort took part the Western countries with France and United Stated being in a leading role at the whole attempt. Moreover, the Arab countries also took part by joining the intervention by having the view that a NATO’s military effort in Libya would help in achieving stability and economic prosperity in the wider region of the Middle East. Nevertheless, all the countries that took part expressed also their own interests as far as the situation in Libya and the factor of the personal interests proved to be a crucial factor that led to the decision to intervene in Libya.
Keywords: Λιβύη--Κοινωνικές συνθήκες; ΝΑΤΟ; Λιβύη--Εξωτερικές σχέσεις; Λιβύη--Σχέσεις--Ηνωμένες Πολιτείες Αμερικής; ΝΑΤΟ; Αραβικές Χώρες; Ηνωμένες Πολιτείες Αμερικής; Εμφύλιος πόλεμος; Λιβύη